Qualidade da informação sobre a ocupação nos casos de Síndrome Respiratória Aguda Grave notificados no SIVEP-Gripe, 2020 - Maira Alves Rocha (2023)
Health information systems (HIS) are widely used in public health to verify vulnerable populations and define priority actions. In the context of the COVID-19 pandemic, the Sistema de Informação da Vigilância Epidemiológica da Gripe (SIVEP-Gripe) was used to monitor cases of compulsory notification of severe acute respiratory syndrome (SARS). In the SARS notification form, occupation is a non-mandatory item. The specialized literature indicates that the occupation presents variable completeness in the different Brazilian HIS. In view of the above, the central hypothesis is that underregistration of the occupation item in SIVEP-Gripe occurs. The objective of the present study was to evaluate aspects of the quality of information on occupation in SARS notifications in the SIVEP-Gripe database, in the five capitals Belém, Belo Horizonte, Goiânia, Porto Alegre and Salvador and two municipalities in Minas Gerais, Betim and Contagem, in year 2020. The research was divided into 3 stages: exploration of the database, interviews with specialists and treatment of the occupation item in SIVEP-Gripe from the anonymized microdata available on the SIS website. The predictive variables considered were age between 20 and 65 years, confirmation of hospitalization, city of residence and notification period between 04/01/2020 to 12/31/2020. The variable of interest was occupation. The descriptive analysis sought to identify the completeness of the occupation item, the methodological clarity of the documents guiding its completion and the occupational major group with the highest concentration of occupational unit groups in each municipality, according to ISCO-88. The statistical software R and the Excel program were used for the analysis. The research was approved by the UFMG Research Ethics Committee. The hypothesis of underregistration of the occupation item was confirmed. As a result, a completeness of 2.24% of the occupation was obtained, classified as very bad, according to the score proposed by Romero and Cunha (2006). The main document that guided the completion of the notification forms, the Guia de Vigilância Epidemiológica – Emergência de saúde pública de importância nacional pela doença pelo Coronavírus 2019, published in different versions in April and August 2020, did not have methodological clarity regarding the occupation item, since they did not even mention it, although it was already included in the notification form since 03/31/2020. As for the occupational major groups, in the capitals MG2 - Professionals was identified as the most frequent, while in the municipalities of Contagem and Betim it was MG7 - Craft and related trades workers and MG9 - Elementary occupations, respectively. Considering the consolidation of the National Worker's and Worker's Health Policy and the need to increase visibility on the illness/work relationship in cases of COVID-19, it is recommended to make occupation a mandatory item in SIVEP-Gripe, establish an evaluation policy and monitoring of the system and carrying out studies involving focus groups with HIS managers to propose improvements.